Capability of Sulphur Oxidizing Bacteria to Inhibit Basal Plate Rot and Increase Shallot Growth on Andisols - Sudadi Sudadi; Hadiwiyono Hadiwiyono; Sumarno Sumarno; Dhani Dhyana Ciptasari (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
In the recent years, basal plate rot (BPR) caused by Fusarium oxysporum f. sp.cepae (FOCe) is one of the important constraints of shallot production in Indonesia. This research aimed to study the potential of S-oxidizing bacteria (SOB) as biological control agents to inhibit FOCe and provide available-S to shallot on Andisols. An experiment in laboratory was conducted to evaluate the capabilty of SOB in oxidizing S in liquid medium and a pot experiment was aimed to evaluate the capability of SOB in providing available-S and inhibiting infection of shallot by FOCe in Andisols. All treatments were arranged by a Completely Randomized Design with three replications. The data were analyzed by F test, followed by Duncan’s Test.The results showed that the capability of oxidizing S in a liquid medium increased after the incubation for six days, with the highest concentration of soluble-S was taken from SOB2 isolate. The isolate provided the highest available-S, while the highest capability of decreasing the disease incidence was taken by SOB3 and SOB1+2+3. SOB3 isolates promoted the highest growth of shallot. So it has a tremendous potential if they are used as an inoculum of bio-fertilizer and biological control agent of BPR of shallot.